WHAT ARE BENEFITS OF USING CREATIVE ENGLISH IN PRIMARY SCHOOL? - Berikboyeva Nigora Ravshanovna (Bright Mind Publishing, 2025)
Using basic vocabulary through individual words and shortened sentences are essential in primary schools. Young children learn differently than teenagers or adults verifying to their native language. Different type of teaching methods helps children to learn the language easily. It depends on the teacher to choose the best choices in teaching English. Best options can be cartoons, art, drawings, songs, short stories or daily dialogs. Besides that, youngsters enjoy playing games in English classroom. There are uncounted techniques to be available to use in teaching children. It is essential to teachers to identify the appropriate activity which is enjoyable for children
Keywords: Cartoons, art-based activities, drawings, songs, short stories, daily dialogs, social interaction